Basic GIS training for upgrading local government spatial planning - Muhammad Izzudin; Stevanus Nalendra Jati; Wijaya Mardiansyah; Januar Eko Aryansah; Ferdiansyah R (Universitas Muhammadiyah Magelang, 2022)
The existence of the Indonesian government's One Map Policy (OMP) demands synergy to the regions. Sumatra is one of the areas that captures this opportunity. One of the follow-up actions to this policy is regional readiness in preparing qualified human resources in the geospatial field. Sriwijaya University as one of the universities in Indonesia that focuses on developing human resources in South Sumatra, facilitates local governments in developing employee capacity. This program was carried out for 5 days to learn about the basic level Geographic Information System (GIS) for Bappeda Lahat employees. This program is carried out in 3 stages, namely identification of partner problems, training, and evaluation. This training program has a positive impact on employees in Bappeda Lahat, namely being able to make location points for regional planning with SmartGPS, making spatial shapefile data and making thematic spatial maps according to the main tasks of the job fields of employees in Bappeda Lahat.